192k views
1 vote
If f(x) and g(x) are equivalent, what must a be?
[f(x) and g(x) in the picture]​

If f(x) and g(x) are equivalent, what must a be? [f(x) and g(x) in the picture]​-example-1

1 Answer

4 votes


(1)/( (1)/(3)x - 2 ) + 5 = (a)/(x - 6) + 5 \\ \\ (a)/(x - 6) = (1)/( (1)/(3)x - 2 ) + 5 - 5 \\ \\(a)/(x - 6) = (1)/( (1)/(3)x - 2 ) \\ \\ a \: ((1)/(3)x - 2) = x - 6 \\ \\ a = (x - 6)/((1)/(3)x - 2) \\ \\ a = (x - 6)/( (x - 6)/(3) ) \\ \\ a = (x - 6) / (x - 6)/(3) \\ \\ a = (x - 6) * ( (3)/(x - 6) ) \\ \\ a = 3

I hope I helped you^_^

User Marva
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.